Identifying level and category shift in Legenda Pulau Senua bilingual storybook - Debi Nurmalina (Mitra Palupi, 2022)
to the TL. Adding occurs because TL has grammatical category which SL lacks. Omitting occurs because the TL has a grammatical category which exists in the SL. Purpose: This study is conducted to analyze translation shifts in Bilingual book story. Design and methods: This study used qualitative research method in the form of content analysis. Data analysis techniques is the process of organizing and sorting data into the patterns, categories and units of the basic description so that it can be determined the theme and can be formulated working hypothesis as based on the data. Results: there were 15 data that indicated translation shift in this book, and the category shift were dominantly used. Any shift in the process of translation is normal, as long as it does not change the meaning or the message of the text.